2023
DOI: 10.3390/nu15153295
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Components of the Mediterranean Diet on Food Allergies: A Systematic Review

Abstract: Allergies are a common and increasing health problem affecting millions of people worldwide. This increase is attributed to genetic predisposition, air pollution, climate change, lack of physical activity, and alterations in eating habits. The Mediterranean diet (MD), which includes a lot of fruits and vegetables, whole grains, legumes, nuts, olive oil, and fish, has been linked to a variety of health benefits, including a lower risk of chronic and allergic disease. This paper explores the effects of the dieta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…A recent systematic review revealed a favorable influence of the MD on the emergence of FAs [60]. This correlation is expected due to the well-established health-promoting and anti-inflammatory characteristics of the MD, which is enriched with essential nutrients such as polyphenols, n-3 long-chain PUFAs, and other fat-soluble nutrients [60].…”
Section: Allergen Avoidance Vs Exposurementioning
confidence: 99%
See 3 more Smart Citations
“…A recent systematic review revealed a favorable influence of the MD on the emergence of FAs [60]. This correlation is expected due to the well-established health-promoting and anti-inflammatory characteristics of the MD, which is enriched with essential nutrients such as polyphenols, n-3 long-chain PUFAs, and other fat-soluble nutrients [60].…”
Section: Allergen Avoidance Vs Exposurementioning
confidence: 99%
“…In a prospective study, Tanaka et al [59] firstly established a positive correlation between maternal caffeine intake during pregnancy and the risk of FAs in children, although the underlying mechanisms remain unclear. In recent years, the healthier Mediterranean diet (MD), characterized by an abundance of fruits and vegetables, whole grains, legumes, nuts, olive oil, and fish, has assumed an important role in FA prevention [60]. A recent systematic review revealed a favorable influence of the MD on the emergence of FAs [60].…”
Section: Allergen Avoidance Vs Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…Dietary patterns and habits seem to be a plausible environmental explanation since they have undergone significant changes in the last decades [13][14][15][16][17][18][19]. Moreover, according to the "diet hypothesis", nutrients and food components may play a fundamental role in the development of allergic diseases by influencing the immune system and allergic inflammation pathways either directly or through the influence on gut microbiota, and thus may promote or protect against allergic diseases [20][21][22][23][24][25]. Considering that diet is one of the most modifiable and readily accessible interventions, the identification of nutrients, food components, or dietary patterns that could be implemented as a preventive or therapeutic strategy for allergic disease seems to be essential.…”
Section: Introductionmentioning
confidence: 99%